2006
DOI: 10.1007/s11224-006-9045-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectroscopic, and structural aspects of two trinuclear cyano-bridged heterometallic complexes

Abstract: Two new cyano-bridged trinuclear heterometallic complexes [Sr 2 (Phen) 4 (CF 3 CO 2 )(H 2 O) 3 Fe(CN) 6 ]·2H 2 O (1) [Ca 2 (Phen) 4 (CF 3 CO 2 )(H 2 O)Co(CN) 6 ]·2H 2 O (2) (where Phen = 1,10-phenanthroline) have been synthesized and their crystal structures have been determined. The structure of complex (1) features a central [Fe(CN) 6 ] 3− unit that links a monocation, [Sr(Phen) 2 (OH 2 )(OOCCF 3 )] + and a dication, [Sr(Phen) 2 (OH 2 ) 2 ] 2+ via two trans cyanide bridges. The complex (2) features a central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The study by Samanta et al [85] reported in the next paper was initiated by remarkable diversity of structural types of cyano-bridged mixed valence complexes. Two novel trinuclear cyano-bridged heterometallic complexes with the formula [M 2 (Phen) 4 (CF 3 CO 2 )(H 2 O) 3 M'(CN) 6 2 .…”
Section: Issuementioning
confidence: 98%
“…The study by Samanta et al [85] reported in the next paper was initiated by remarkable diversity of structural types of cyano-bridged mixed valence complexes. Two novel trinuclear cyano-bridged heterometallic complexes with the formula [M 2 (Phen) 4 (CF 3 CO 2 )(H 2 O) 3 M'(CN) 6 2 .…”
Section: Issuementioning
confidence: 98%
“…Secondly, the broad span of coordination numbers of alkaline earth metals makes the topologies of the resulting coordination polymers difficult to control. Some rare examples of Fe-Sr heterometallic coordination complexes have been reported (Xu et al, 2015;Herbert et al, 2013;Samanta et al, 2006;Prodius et al, 2006), and most of them are trinuclear (Samanta et al, 2006;Prodius et al, 2006) or tetranuclear complexes (Herbert et al, 2013), or one-dimensional chain structures (Xu et al, 2015). Until now, no Fe-Sr heterometallic coordination polymers have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Cyano-bridged bimetallic complexes have been a longstanding research interest of our group [16][17][18][19][20]. In this paper, we focus on pentacyanidonitrosylferrate(II) [Fe(CN) 5 -(NO)] 2-anion considering its rich photochromic and photomagnetic properties and we report a new heterobimetallic one-dimensional polymeric complex [Ni(baepn)(l-NC)Fe(CN) 3 (NO)(l-CN)] n Á3H 2 O.…”
Section: Introductionmentioning
confidence: 99%